Aportaciones criminológicas a la comprensión de la corrupción transnacional - Olasolo, Héctor; Villarraga Zschommler, Luisa Fernanda; Linares Botero, Sofia (Pontificia Universidad Católica del Perú, 2023)
This article studies different criminological perspectives that help to fathom the phenomenon of transnational corruption. To this end, we will first study the characteristics of contemporary societies from different criminological viewpoints and then explain how these contribute to the study and comprehension of transnational corruption. In addition, multiple criminological perspectives will be analyzed, such as white-collar and mass media criminology, victimology, green and maldevelopment criminology, crimes of globalization and macrocriminality, among others.

El presente artículo estudia diferentes perspectivas criminológicas que ayudan a entender el fenómeno de la corrupción transnacional. Con ese fin se estudiarán, en primer lugar, las características de las sociedades contemporáneas desde diferentes perspectivas criminológicas para, después, explicar cómo estas aportan en el estudio y la comprensión de la corrupción transnacional. Asimismo, se analizarán múltiples perspectivas como la criminología de los poderosos y de los medios de comunicación, la victimología, la criminología verde y del maldesarrollo, los crímenes de la globalización y la macrocriminalidad, entre otros.
Criminological Contributions for the Comprehension of Transnational Corruption
Keywords: Transnational Organized Crime; Corruption; Criminological Perspectives; Public Institutions; Private Interest; Crimen Organizado Transnacional; Corrupción; Perspectivas Criminológicas; Instituciones Públicas; Interés Privado; https://purl.org/pe-repo/ocde/ford#5.05.01